DISTRIBUTION OF CHEMICAL ELEMENTS IN KIDNEY SPECIMENS OF PATIENTS WITH SYSTEMIC HYPERTENSION - O. A. Osipova; R. N. Shepel; A. A. Comisov; P. G. Osipov; K. G. Plaksina; N. V. Malay (Российский кардиологический журнал, 2017)
Aim. To assess quantitative macroelement contents of kidney tissue in arterial hypertension (AH) patients.Material and methods. By the method of nephrobiopsy, in AH patients (n=12, duration of AH 6,3±1,5 y.) during surgery on upper urinary tract, specimens were collected of biological tissue of kidney. As the controls, elements in kidney tissue of healthy persons were studied, from those died in traffic accidents (n=18). Mean age of the patients was 48,3±1,6 y.o. By the method of atom-emission spectrometry with nanotechnologies: scanning (SEM; FEI Quanta 200, FEI Quanta 600) and scanning transmission electronic microscopy (STEM; FEI Nova NanoSEM) the contents of macroelements and microelements were assessed.Results. It was found that concentration of atomic C in AH patients comparing to control group shows tendency to increase, exceeding the controls by 9%. In AH patients kidney tissue shows significant decrease of all main elements (N, O, Na, Mg, P, S, Cl, K, Zn).Conclusion. Further study on the mechanisms of AH development with evaluation of chemical elements concentration directly in the tissues where do chemical reactions act, is important for understanding of the grade of involvement of specific organs into these processes. Creation of database of overall element contents of biological tissues is a novel direction in cardiology. The results of elements assessment of kidney tissue in cardiovascular diseases will open new opportunities for treatment and target organ damage prevention.